Framing Effects on Attitudes and Intentions Toward Shark Meat Consumption in Lima, Peru - Biffi, Daniella; Richards, Adam S.; Weinburgh, Molly (Frontiers in Conservation Science, 2022)
Peru has one of the major shark fisheries in the world. Moreover, shark meat consumption is popular and the main commercially exploited species are considered threatened. Recent studies have found high mislabeling rates and high concentrations of methylmercury in shark meat. The purpose of this study is to explore the effectiveness of different framing messages in persuading fish consumers to avoid shark meat consumption and promote sustainable fish (“popular fish”) consumption. Specifically: To what extent do intrinsic and extrinsic risk messages differ in terms of deterring the intention to eat shark meat and promoting the consumption of popular fish, in the presence or absence of an efficacy message about mislabeling of shark meat? The three message frames were: intrinsic (sharks have mercury), extrinsic (sharks are threatened), and efficacy (sharks are mislabeled). The experiment had a factorial design of 2 x 2 x 2 (present vs. absent for each message). Participants (n = 285), surveyed through an online questionnaire, were assigned to one of eight experimental conditions. Participants then completed a survey regarding their intentions and attitudes towards shark meat and popular fish consumption. Attitudes and intentions towards consuming shark meat were discouraged in all experimental conditions. Moreover, the mislabeling message did not reduce participants’ perceived response efficacy (how effective the recommendations for dealing with the problem are), but enhanced it. This study suggests that not all consumers’ attitudes about sharks are negative or that a negative attitude does not affect shark consumption in an adverse way. More research targeting different audiences is needed to determine the optimal approach for promoting sustainable seafood that is also healthy for consumers.